2020
DOI: 10.1007/s13205-020-02471-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of ACE2 orthologues to predict animal host range with high susceptibility to SARS-CoV-2

Abstract: SARS-CoV-2, which causes severe pneumonia epidemics, probably originated from Chinese horseshoe bats, but the intermediate and host range is still unknown. ACE2 is the entry receptor for SARS-CoV-2. The binding capacity of SARS-CoV-2 spike protein to ACE2 is the critical determinant of viral host range and cross-species infection. Here, we used an in silico approach to predict the potential animals range with high susceptibility to SARS-CoV-2 by modelling and studying the Spike–ACE2 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…The analysis of ACE2 protein conservation across species, the modelling of the S viral protein with ACE2 [195][196][197][198] and animal infection models [199][200][201][202][203][204][205][206][207][208][209][210][211] have highlighted the [170,171,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]. Figure 5 was created with BioRender.com.…”
Section: Transmission Of Sars-cov-2 From Humans To Animalsmentioning
confidence: 99%
“…The analysis of ACE2 protein conservation across species, the modelling of the S viral protein with ACE2 [195][196][197][198] and animal infection models [199][200][201][202][203][204][205][206][207][208][209][210][211] have highlighted the [170,171,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]. Figure 5 was created with BioRender.com.…”
Section: Transmission Of Sars-cov-2 From Humans To Animalsmentioning
confidence: 99%
“…(24) Therefore, hACE2R might be another potential target for inhibiting the viral attachment with the host cells. (16)(17)(18) Our results demonstrate that amentoflavone, berbamine, betulinic acid, betulonic acid, cepharanthine, glucogallin, papyrifl avonol A, tomentin A and E exhibited good binding affinity with hACE2R protein, where amentoflavone and berbamine showed a strong binding capacity with this protein. Moreover, ABL1 and calcineurin-NFAT also play an important role in SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 67%
“…Molecular docking simulations were used to perform in silico screening of potential active compounds against hACE2R, 3CL PRO , PL PRO , RdRp, nsp10, nsp13-16, calcineurin-NFAT, transmembrane protease serine 2 (TMPRSS2), and ABL1. (16)(17)(18) In this respect, numerous plants containing high concentrations of flavonoids and polyphenolic compounds are known to have antioxidant, anticancer, anti-depressant, anti-infl ammatory, anti-diarrheal, antidiabetic, and anti-viral effects. Furthermore, a recent study showed that above mentioned compounds exert anti-SARS-CoV-2 activity with inhibitory concentration 50/effective concentration 50 less than 10 μmol/L.…”
mentioning
confidence: 99%
“…With respect to ungulate species, three cervids were rated as having ACE2 receptor sequences with a high propensity for binding SARS-CoV-2, and 21 artiodactyls scored as medium (including domestic cattle, sheep, goats, and water buffalo) [150]. A similar study comparing ACE2 protein sequences in humans and 22 nonhuman animal species (including six ungulates) concluded that C. dromedarius and O. aries have a higher binding affinity to SARS-CoV-2 compared to humans, while alpaca (Vicugna pacos) have a binding affinity about equal to that of humans, and E. caballus and Przewalski's wild horse (Equus prezwalskii) have lower binding affinities [151].…”
Section: Other Hooved Speciesmentioning
confidence: 99%